2020
DOI: 10.1186/s13023-019-1286-z
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary haemorrhagic telangiectasia and pregnancy: a review of the literature

Abstract: Background: Hereditary haemorrhagic telangiectasia (HHT) is a dominantly inherited genetic vascular disorder that has prevalence of 1:5000 to 1:8000, and which is characterised by recurrent epistaxis, cutaneous telangiectasia, and arteriovenous malformations (AVMs) that affect many organs including the lungs, gastrointestinal tract, liver, and central nervous system. The aim here was to carry out a review of the literature on HHT complications during pregnancy in order to guide management decisions. Main body:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 47 publications
2
36
0
4
Order By: Relevance
“…These physiologic factors can promote enlargement and rupture of PAVMs during pregnancy. Numerous cases of PAVM-related complications during pregnancy have been reported in the literature, most frequently hemothorax [45][46][47][48][49][50][51]. However, despite acknowledgement of this greater risk during pregnancy, international consensus guidelines do not provide specific recommendations about treatment of PAVMs during pregnancy [18].…”
Section: Pavms In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…These physiologic factors can promote enlargement and rupture of PAVMs during pregnancy. Numerous cases of PAVM-related complications during pregnancy have been reported in the literature, most frequently hemothorax [45][46][47][48][49][50][51]. However, despite acknowledgement of this greater risk during pregnancy, international consensus guidelines do not provide specific recommendations about treatment of PAVMs during pregnancy [18].…”
Section: Pavms In Pregnancymentioning
confidence: 99%
“…These risk estimates, although imperfect, do underscore the danger of untreated PAVMs in pregnancy. A recent review examining pregnancy in HHT concluded similarly that the current maternal mortality and morbidity risks quoted in the literature are likely underestimations, and that these cases should be considered high risk [51]. The British Thoracic Society describes pregnancy as a relative contraindication to elective embolization due to radiation exposure and risk of preterm labor [1].…”
Section: Pavms In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…were only focused on patients with HHT, and patients without HHT were not included. Although in our patients ruptured PAVMs happened with no clear triggers, some authors have reported that pregnancy and pulmonary hypertension could be risk factors for PAVMs rupture [ 26 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 63%
“…Mucocutaneous telangiectasias at characteristic sites including the nose, fingers, and oral cavity, and 4. First-degree relative with HHT ( Dupuis et al, 2020 ). In contrast, GTN usually presents following a pregnancy with abnormal vaginal bleeding and a plateau or rise of HCG levels.…”
Section: Discussionmentioning
confidence: 99%